2009
DOI: 10.1177/1933719108329095
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Pregnancy

Abstract: Inflammation is a process by which tissues respond to various insults. It is characterized by upregulation of chemokines, cytokines, and pattern recognition receptors that sense microbes and tissue breakdown products. During pregnancy, the balance of Th1 (cell-mediated immunity) and Th2 (humoral immunity) cytokines is characterized by an initial prevalence of Th2 cytokines, followed by a progressive shift toward Th1 predominance late in gestation, that when is abnormal, may initiate and intensify the cascade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
639
6
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(669 citation statements)
references
References 89 publications
10
639
6
14
Order By: Relevance
“…Preeclampsia is considered a disorder strongly related to oxidative stress [1], [2], [6], [8], [11]- [13], [16]- [18]. But even in normal pregnancy there is evidence of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preeclampsia is considered a disorder strongly related to oxidative stress [1], [2], [6], [8], [11]- [13], [16]- [18]. But even in normal pregnancy there is evidence of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Due to metabolic changes and low grade inflammation, pregnancy is a condition of increased susceptibility to oxidative stress [1], [2]. Several organs in pregnancy show increased basal oxygen consumption and changes in substrate energy use resulting in increased mitochondrial mass and production of reactive oxygen species (ROS) [3].…”
mentioning
confidence: 99%
“…Production of MMP-1, MMP-3 and MMP-9 from resident fibroblasts (Ito et al, 1991) and smooth muscle cells (Watari et al, 1999) may also be increased by IL-1β in the cervix whilst downregulating the expression of tissue inhibitor of metalloproteinase (TIMP)-2, an endogenous inhibitor of MMP-2 (Watari et al, 1999), with these events being further amplified by NF-κB production. NF-κB itself may be A c c e p t e d M a n u s c r i p t activated via toll-like receptor (TLR)-4 by degraded extracellular matrix proteins such as fragments of fetal fibronectin, degraded during cervical remodelling, thus reinforcing the ongoing sterile inflammation of labour (Challis et al, 2009). Thus, at the end of pregnancy and during labour, the cervix having remained firm and closed despite increasing pressure during pregnancy, begins, under the influence of a host of inflammatory mediators, to soften and dilate.…”
Section: The Cervixmentioning
confidence: 99%
“…This could be explained by the fact that IL-6 has both pro-and antiinflammatory properties. The classification of IL-6 as a Th1-type cytokine in studies on preterm labor 56,57 or as a Th2 type cytokine in early pregnancy [58][59][60][61] remains controversial. Recently, it has been demonstrated that IL-6 is involved in the promotion of Th2 differentiation and the inhibition of Th1 polarization.…”
Section: Commentmentioning
confidence: 99%